QUALITY OF SERVICES OF MEDICAL INSTITUTIONS - AN ACTUAL PROBLEM OF HEALTHCARE MANAGEMENT - KALINICHENKO, Sergiy; KHARCHEVNIKOVA, Liliia; AVRIATA, Andrii; OLIINYK, Ihor (Herald of Khmelnytskyi National University. Economic sciences, 2023)
In the conditions of the modern socio-economic situation, health care reforms, and a new competitive environment, medical organizations are looking for ways to improve the quality of services and the efficiency of their activities. It is obvious that there is a direct relationship between the quality of management and the effectiveness of management. Quality is one of the factors that determines the effectiveness of a medical service and is the most important factor in increasing market share, contributes to sustainability in competitive conditions in conditions of limited funding and rapid changes in the external environment, which helps to reduce costs, which contributes to the overall increase in the efficiency of medical activity. These rights of citizens are enshrined in the Constitution, which proves their importance for society and the state, but then they are filled with a special meaning, subject to industry regulation. Institutes of health care and medical and social care are complex, covering legal norms that establish, regulate and protect the ownership of these rights to specific persons (civil, administrative, criminal, environmental norms, etc.). The quality of medical care is the main target function, as well as the criterion of the health care system's activity from the lower level to the top of the Ministry of Health. Quality is ensured by all components of the health care system: material and technical support, personnel, scientific, organizational, financial, and informational resources. The result of the health care system is determined by its construction, functioning, order of interaction of elements. It follows that the basis of quality improvement is a change in the system itself. Management structures and mechanisms can support and improve the performance of the system during the reform process.
Keywords: health care; management; quality; system; services